(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
To minimize the expenditure of electrical energy for communal waste water biological treatment the simulation and investigation of oxygen transfer efficiency in aeration tank have been made. Soluted oxygen transfer efficiency ? 0 (Fig.1.) is one of the main important factor directly estimating the expenditure of electrical power for waste water aeration. The research object is an aeration tank (Fig.2.) with one input impact -–the air blower’s capacity Lg (m3/h), one output controlled parameter – dissoved oxygen concentration C (g/m3) and several perturbances such as waste water temperature T (oC), waste water afflux Q (m3/h) and biological oxygen need La (g/m3) for complete purification. Oxygen’s transfer efficiency depends on the waste water temperature, the depth of aerator immersion h (m), air flow intensity ? d (m3/disc.h) and the air diffusor’s density ? s. For simulation and practical design of the air blower control system the equations of statics C=f(Lg, Q, La, T, h, ? d , ? s) and dynamics C=f(t) have been compiled. That made possible to estimate the static gains for control channel Ka and for perturbances Kq, KT as well as the time constant of the aeration tank Ta. The analysis prove that the aeration tank is a non-stationary control object with the variable static and dynamic parameters and needs adaptive controller with predication of oxygen consumption. The block diagram for transient process simulation of the oxygen concentration control system have been compiled using model of the actual PID controller and the “Matlab” subprogram “Simulink”.